(untitled) (Bangladesh Rice Journal, 2016)
Crop-cut is a widely used and well accepted procedure for estimating rice yield. This yield is then multiplied by the area planted under rice cultivation to determine rice production of the country. In Bangladesh, crop-cut is used to estimate transplanted rice yield. Department of Agricultural Extension (DAE) and Bangladesh Bureau of Statistics (BBS) as the public agencies provide estimate on area and production of rice but they use different methods of crop-cut. The estimates of these two agencies on area and production of rice are different posing a question to the users on the reliability of the estimates. An attempt has been made with the objective to formulate a protocol that provides reliable and unique estimates on rice area and production. It is suggested to make at least three cuts in each plot to minimize the chance of over or under estimation of the whole plot yield and the radius of the circle should be 178.5cm so that the cut area becomes 10 m2 in order to easy conversion of the crop-cut yield to t ha-1. Bangladesh Rice j. 2016, 20(1): 11-16